The Impact of Political Brand Relationship Quality and Brand Engagement on Voters’ Citizenship Behaviour: Evidence from Indonesia - Farhan, Akhmad; Omar, Nor Asiah; Jannat, Taslima; Nazri, Muhamad Azrin (The South East Asian Journal of Management, 2020)
Research Aims: Recently, the usage of branding has become more popular in non-traditional social markets such as politics due to decreasing political participation. This study investigates how political brand relationship quality (satisfaction and trust) influences political brand engagement (PBE) and voters' citizenship behaviour (VCB). Design/Methodology/Approach: The current study collected data from voters who are located in Jakarta and participated in the Indonesian presidential election of 2014. A total of 520 voters participated. Data were collected via quota sampling and drop-off survey and were analysed using structural equation modelling. Research Findings: The empirical findings suggest that satisfaction has the strongest impact on political party brand engagement, while trust has the strongest impact on voters' citizenship behaviour. Further results imply that political brand engagement contributes to voters' citizenship behaviour, as well as significantly mediates the relationship between political brand relationship quality (satisfaction and trust) and voters' citizenship behaviour. Theoretical Contribution/Originality: This study is based on social exchange theory and source credibility theory. The findings of this study have theoretical implications in that the results lend support to the appropriate role of brand relationship quality and brand engagement in creating voters' citizenship behaviour. Managerial Implication in the Southeast Asian Context: The findings of this study add new insights to the political branding literature as well as strategic guidelines for the political parties that are planning to build a relationship with voters. As a way to improve voters' perceptions in Southeast Asia, political parties should adapt conventional marketing theory to a political marketing setting, and implement marketing programmes that keenly engaged with voter's behaviour. Research Limitation and Implications: This study bears several limitations. First, the current study was conducted in the capital city of Indonesia, thus limiting the scope of the research. Second, this study was restricted to a political party. It would be interesting if future studies examine political candidates as a brand.